(untitled) - Craven, Miles (Thành phố Hồ Chí Minh, 2014)
Pass the TOEIC test is a thoroughly comprehensive, authentic, and up-to-date preparation course for the TOEIC test. Ideal for self-study or class use, the course builds confidence and boots test scores for students on the listening and reading sections of the TOEIC test
Keywords: English language,Test of English for International Communication,Anh văn giao tiếp quốc tế (TOEIC),Tiếng Anh; Study and teaching,Dạy và học